The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00774-015-0679-x
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with cyclophosphamide, epirubicin and 5-fluorouracil causes trabecular bone loss, bone marrow cell depletion and marrow adiposity in female rats

Abstract: The introduction of anthracyclines to adjuvant chemotherapy has increased survival rates among breast cancer patients. Cyclophosphamide, epirubicin and 5-fluorouracil (CEF) combination therapy is now one of the preferred regimens for treating node-positive breast cancer due to better survival with less toxicity involved. Despite the increasing use of CEF, its potential in causing adverse skeletal effects remains unclear. Using a mature female rat model mimicking the clinical setting, this study examined the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 44 publications
6
35
0
Order By: Relevance
“…Consistent with a multiplicity of functions for OPN, it is involved specifically in both the forming and resorption of bone. That is why its suppression causes defects in process of bone remodeling (Fan et al, 2016) In The result of present work came in line with the study of Xian et al (2008) who found that MTX had no obvious effects on apoptosis but only some moderate damaging effects on proliferation of osteoblasts and preosteoblasts in bone with moderate changes in osteoblastic cell density along trabecular surface in comparing to 5-FU.…”
Section: Results:-supporting
confidence: 80%
“…Consistent with a multiplicity of functions for OPN, it is involved specifically in both the forming and resorption of bone. That is why its suppression causes defects in process of bone remodeling (Fan et al, 2016) In The result of present work came in line with the study of Xian et al (2008) who found that MTX had no obvious effects on apoptosis but only some moderate damaging effects on proliferation of osteoblasts and preosteoblasts in bone with moderate changes in osteoblastic cell density along trabecular surface in comparing to 5-FU.…”
Section: Results:-supporting
confidence: 80%
“…Our data shows that a clinically relevant dose of carboplatin in healthy mice induces trabecular bone loss (decrease in Tb.BV/TV, Tb.N, and Conn.D and an increase in Tb.Sp in the distal femur and proximal tibia of mice treated with carboplatin). These findings are supported by studies that reported combination chemotherapy treatment of 5-fluorouracil, cyclophosphamide, and epirubicin caused trabecular bone loss in rats [ 28 ] and that Folfiri (5-fluorouracil, leucovorin and irinotecan) caused loss of muscle and bone mass [ 14 ]. Additionally, data suggests that cisplatin, another platinum-based chemotherapy drug, induces a decrease in Tb.BV/TV in the proximal tibia of rats [ 12 ].…”
Section: Discussionmentioning
confidence: 55%
“…Osteoblast density was obtained by counting cuboidal mononuclear cells along the trabecular surface in six sequential images along primary spongiosa, and expressed as osteoblast number per mm 2 trabecular bone area. TRAP+ multinuclear osteoclasts were counted under light microscopy and expressed as cells per mm 2 trabecular bone area in the secondary spongiosa as described [31,32]. Adipocytes within bone marrow area were counted in four random images within the lower secondary spongiosa region, and expressed as adipocyte number per mm 2 marrow area [7,10].…”
Section: Methodsmentioning
confidence: 99%